KONSEP TOTAL QUALITY MANAGEMENT DAN SERVICE QUALITY DALAM PENGEMBANGA PENDIDIKAN TINGGI ISLAM (Sebuah konsep Pengembangan TQM dan SQ untuk Fakultas Sains dan teknologi) - Rusdiana Rusdiana Rusdiana (JURNAL ISTEK, 2013)
Quality is at the top of most agenda and improving quality is probably the most important task facing any situation. Of course, we all know quality when we experience it, but describing and explaining it is a more difficult task. In our everyday life, we usully take quality for granted, especially when it is regularly provided. The best organizations, whether public or private, understanding quality and know its secret. While, service quality characteristics especially education, are more difficuli to define than those for physical products. This because the in¬clude many important subjective elements. For purposes of analysing quality it is more appropriate to view education as a service industry than as a production process. In TQM, staff members are known as internal customers and students or learners are primary external customesr or clients. This article describes Total Quality Management and Service Quality for improving higher education organization. Two cases in Total Quality Management, and Service Quality are discussed and analyzed to show a little example of higher education organization in Indonesia that has not been performed Total Quality Management and Service Quality yet. The Result of the analysis proves this. Then, authors also show how Total Quality Management as the philosophy can be achieved in higher education organization.quality culture.